Kakovost v jezikovnem testiranju - Ferbežar, Ina (Jezik in slovstvo, 2019)
The article presents the education programme Slovenian as a Second and Foreign Language and the context in which it was established. Critical issues are raised regarding the programme and the system of testing and certifying Slovenian as a second and foreign language based on the programme. The Slovenian language exams that have been in place since 2015 were developed according to international quality standards. The article gives a more detailed presentation of the three most critical standards: comparability of test versions, reliability of rating, and analysis of test results.
Keywords: izobraževalni jezikovni programi; izobraževalni programi za odrasle; jezikovno testiranje; Skupni evropski jezikovni okvir; slovenščina kot drugi in tuji jezik; standardi kakovosti